Preparation method for rapidly preparing BMO piezoelectric catalyst growing on different crystal faces and application of BMO piezoelectric catalyst

By using potassium ferrocyanide to regulate crystal surface growth and optimizing hydrothermal reaction conditions during the preparation of Bi2MoO6 catalyst, the problem of difficulty in forming a two-dimensional nanosheet-like structure in the prior art was solved, and efficient and stable catalyst preparation was achieved, which significantly improved its piezoelectric performance and application performance.

CN119869504APending Publication Date: 2025-04-25GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510064834.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, when preparing Bi2MoO6 piezoelectric catalyst, it is difficult to effectively form a two-dimensional nanosheet-like structure, resulting in limited piezoelectric properties of the catalyst and insufficient in terms of material purity, crystal integrity and performance stability.

Method used

By configuring the Bi suspension and Mo source solution, potassium ferricyanide is added as the crystal surface regulator, and hydrothermal reaction is carried out in an autoclave, the reaction conditions and steps are optimized, including adjusting the pH value and pretreating the mixed solution to achieve specific crystal surface growth of Bi2MoO6 and efficient preparation.

Benefits of technology

The two-dimensional nanosheet-shaped 002 crystal plane growth of Bi2MoO6 catalyst is achieved, with a band gap range of 2.1 to 2.5 eV, which significantly improves the piezoelectric performance and electronic transition efficiency of the catalyst, improves the purity, structural stability and chemical consistency of the material, and enhances the practical application breadth and life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869504A_ABST
    Figure CN119869504A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional material preparation, and discloses a preparation method and application for rapidly preparing BMO piezoelectric catalysts growing on different crystal faces, and the preparation method comprises the following steps: preparing a Bi suspension and a Mo source solution; slowly adding the Mo source solution into the Bi turbid liquid under a stirring condition to form a uniformly mixed solution; adjusting the pH value of the mixed solution to 5-7 by using a sodium hydroxide solution; adding potassium ferricyanide into the mixed solution as a crystal face regulating agent; pretreating the mixed solution; putting the treated mixed solution into a high-pressure reaction kettle for hydrothermal reaction; cooling to room temperature, collecting a reaction product, washing with absolute ethyl alcohol and deionized water in sequence, and drying to obtain the Bi2MoO6 catalyst with a specific crystal face structure. According to the invention, through crystal face regulation and process optimization, the two-dimensional nanosheet BMO catalyst with high purity and stable structure is prepared, and higher piezoelectric catalytic performance and reusability are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional material preparation, and in particular to a method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes and its application. Background Art

[0002] Bi2MoO6 (BMO), as a functional material with excellent piezoelectric catalytic properties, is widely used in wastewater treatment and pollutant degradation. Its catalytic performance is significantly affected by the crystal face structure. The selective growth of different crystal faces can regulate the morphology and band gap characteristics of the material, thereby optimizing the catalytic performance.

[0003] In the prior art, some studies have achieved the growth of specific crystal planes of BMO materials by introducing templates, surfactants or regulating the reaction temperature. For example, by controlling the crystallization behavior of reactants through templates, BMO materials with block or granular structures can be formed, which show good light absorption characteristics and stability in photocatalytic applications. In addition, by regulating the reaction temperature, the crystallinity of the material can be increased and its antioxidant properties can be improved.

[0004] Although existing technologies have made certain progress in the regulation of specific crystal planes, there are still some shortcomings; first, existing methods fail to effectively form two-dimensional nanosheet structures, which are crucial to the improvement of specific surface area and active sites, resulting in limited piezoelectric properties of catalysts; second, existing methods have difficulty in balancing material purity and crystal integrity, and residual impurities in the product will affect the catalytic performance; finally, existing catalysts have poor performance stability after multiple cycles, limiting the breadth and life of their practical applications. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a preparation method and application of BMO piezoelectric catalysts that can quickly grow on different crystal planes, which solves the problems in the prior art of low crystal plane regulation efficiency and difficulty in forming highly active two-dimensional nanosheet structures.

[0006] To achieve the above object, the present invention is implemented by the following technical scheme: a method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes, comprising the following steps:

[0007] Prepare Bi suspension and Mo source solution;

[0008] The Mo source solution is slowly added to the Bi suspension under stirring conditions to form a uniform mixed solution;

[0009] Adjust the pH of the mixed solution to 5-7 with sodium hydroxide solution;

[0010] adding potassium ferrocyanide as a crystal surface regulating agent to the mixed solution;

[0011] Mixed solution pretreatment;

[0012] placing the treated mixed solution in a high pressure reactor for hydrothermal reaction;

[0013] After cooling to room temperature, the reaction product was collected, washed with anhydrous ethanol and deionized water in sequence, and dried to obtain a Bi2MoO6 catalyst with a specific crystal face structure.

[0014] Preferably, the preparation of Bi suspension and Mo source solution comprises:

[0015] Dissolve 1.25-1.75 mmol (Bi(NO3)3·5H2O) in 30 mL of deionized water, and use ultrasound to evenly disperse Bi particles to obtain a Bi suspension.

[0016] Dissolve 0.25-0.75 mmol sodium molybdate (Na2MoO6·2H2O) in 100 mL deionized water and stir for 5-10 minutes until it is completely dissolved to obtain a Mo source solution.

[0017] Preferably, the step of mixing the solution comprises:

[0018] Under magnetic stirring, slowly add the Mo source solution at a rate of 5-10 mL / min;

[0019] After the dropwise addition is completed, stirring is continued for 30 to 60 minutes to make the reaction system fully uniform.

[0020] Preferably, the step of adjusting the pH of the mixed solution comprises:

[0021] Use 1.5-4.0 mol / L NaOH solution to add dropwise into the mixed solution;

[0022] Real-time monitoring of the pH value of the solution;

[0023] After the conditioning was completed, stirring was continued for 30 minutes to stabilize the solution.

[0024] Preferably, the step of adding potassium ferrocyanide to the mixed solution comprises:

[0025] Add 0.01-0.1 mmol potassium ferrocyanide K3[Fe(CN)6];

[0026] Stir for 10 to 20 minutes to ensure that potassium ferrocyanide is evenly distributed in the solution to regulate the growth of the crystal surface.

[0027] Preferably, the step of hydrothermal reaction comprises:

[0028] The treated mixed solution is transferred to a polytetrafluoroethylene-lined autoclave;

[0029] The reaction is carried out at 180 to 200° C. for 10 to 15 hours;

[0030] After the reaction was completed, it was cooled to room temperature.

[0031] Preferably, the product treatment step after cooling comprises:

[0032] Wash alternately with anhydrous ethanol and deionized water, with each wash volume of 20-50 mL, for a total of three washes;

[0033] The washed product is placed in an oven and dried at 60-80°C for 10-12 hours.

[0034] Preferably, the Bi2MoO6 catalyst with a specific crystal plane structure includes:

[0035] When the crystal plane is 002, the catalyst appears as a two-dimensional nanosheet with a band gap ranging from 2.1 to 2.5 eV;

[0036] When the crystal plane is 131, the catalyst is in block form and its band gap ranges from 2.7 to 3.1 eV.

[0037] Preferably, the mixed solution pretreatment step comprises:

[0038] The mixed solution is subjected to ultrasonication for 10 minutes and then stirred for 10-20 minutes to promote the full dissolution and dispersion of the substances in the precursor to promote the full mixing and uniform dispersion of the precursor;

[0039] During the ultrasonic stirring process, the pH value of the mixed solution is maintained stable at 5 to 7 to ensure the chemical stability of each component in the solution.

[0040] The present invention also provides an application method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes. The BMO piezoelectric catalyst includes but is not limited to application in the degradation of 2,4-dichlorophenol (2,4-DCP):

[0041] The initial concentration of the target pollutant was 10 mg / L, and the catalyst dosage was 100 mg;

[0042] An ultrasonic generator was used to provide external stress, with an ultrasonic frequency of 40kHz and a power of 100W;

[0043] Under the above conditions, the degradation efficiency exceeded 96%.

[0044] The present invention provides a preparation method and application of a BMO piezoelectric catalyst for rapid preparation of different crystal plane growths, which has the following beneficial effects:

[0045] 1. The present invention achieves the directional growth of specific crystal planes of Bi2MoO6 by adding potassium ferrocyanide and optimizing the hydrothermal reaction conditions, preferentially forms two-dimensional nanosheet 002 crystal planes, reduces the band gap to 2.1-2.5 eV, significantly improves the piezoelectric properties and electronic transition efficiency of the catalyst, and optimizes the catalytic activity.

[0046] 2. The present invention improves the uniformity of the reaction system and the stability of ion distribution through the pretreatment step of heating the mixed solution and stabilizing the pH value, provides a controllable initial condition of the chemical environment for crystal growth, and improves the performance and production consistency of the catalyst.

[0047] 3. The present invention removes impurities and by-products in the solution by alternately washing with anhydrous ethanol and deionized water and drying at low temperature under vacuum conditions, while protecting the integrity of the crystal structure, so that the catalyst has higher purity, stronger structural stability and chemical consistency. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Please see attached Figure 1 The embodiment of the present invention provides a method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes, comprising the following steps:

[0051] Prepare Bi suspension and Mo source solution. Bi source and Mo source are the main components of Bi2MoO6 (BMO) crystals. In the solution, they exist in the form of ions. The dissolution process lays the foundation for uniform mixing.

[0052] The Mo source solution is slowly added to the Bi suspension under stirring conditions to form a uniform mixed solution. By slowly adding, the Mo ions are prevented from being locally oversaturated in a short time, the uniformity of the mixed solution is ensured, and crystal defects are reduced.

[0053] The pH of the mixed solution is adjusted to 5-7 with a sodium hydroxide solution. By adjusting the pH of the mixed solution, the structure of the precursor is optimized to ensure the selectivity of different crystal faces in the subsequent crystal growth process;

[0054] Potassium ferrocyanide is added to the mixed solution as a crystal face regulator. Potassium ferrocyanide regulates the growth rate of the crystal and promotes the selective growth of specific crystal faces, thereby increasing the proportion of the two-dimensional nanosheet morphology of the catalyst, enhancing the piezoelectric performance, and optimizing the functional characteristics of the catalyst.

[0055] Pretreatment of the mixed solution improves the uniformity and stability of the precursor and provides good conditions for crystal growth in the hydrothermal reaction;

[0056] The treated mixed solution is placed in a high-pressure reactor for hydrothermal reaction. The hydrothermal reaction promotes the growth and directional arrangement of crystals under high temperature and high pressure conditions, thereby improving the structural integrity and catalytic performance of the material;

[0057] After cooling to room temperature, the reaction product is collected, washed with anhydrous ethanol and deionized water in turn, and dried to obtain a Bi2MoO6 catalyst with a specific crystal face structure. The residual unreacted substances and by-products are removed by washing, and the product is dried to ensure the crystalline integrity and purity of the product, so that the prepared catalyst has high purity and a specific crystal face structure.

[0058] Please see attached Figure 1 In a preferred embodiment of the present invention, the preparation of Bi suspension and Mo source solution comprises:

[0059] 1.25-1.75 mmol (Bi(NO3)3·5H2O) was dissolved in 30 mL of deionized water, and the Bi particles were uniformly dispersed with the aid of ultrasound to obtain a Bi suspension. After the Bi source and the Mo source were mixed, the Ksp of Bi2MoO6 was much lower than that of bismuth nitrate, resulting in the conversion of bismuth nitrate into bismuth molybdate. This process can avoid interference from other substances that may exist in the solvent (deionized water), and can also accurately control the ratio of Bi to Mo elements to avoid the generation of other types of bismuth molybdate, thereby ensuring the controllability of the preparation process and the quality of the catalyst.

[0060] Dissolve 0.25-0.75 mmol sodium molybdate (Na2MoO6·2H2O) in 100 mL deionized water and stir for 5-10 minutes until completely dissolved to obtain a Mo source solution. Sodium molybdate is used as a Mo source. 6+ The main source of molybdenum ions, whose dissolution behavior directly affects the concentration of molybdenum ions in subsequent reactions, is provided by sodium molybdate. 6+ The ion concentration ensures uniform reaction when mixed with the Bi suspension, providing sufficient and stable supply of molybdenum ions for crystal growth, thereby improving the structural integrity of the catalyst.

[0061] Please see attached Figure 1 In a preferred embodiment of the present invention, the step of mixing the solution comprises:

[0062] Under magnetic stirring conditions, the Mo source solution was slowly added at a rate of 5-10 mL / min. The purpose of slowly adding the Mo source solution was to control the Mo 6+ The introduction rate of ions can be controlled to avoid excessive local concentration of Mo ions due to excessive dropwise addition, which may cause precipitation or uneven distribution. At the same time, the magnetic stirrer can enhance the convection of the solution and promote the 3+ and Mo 6+ The full contact of ions provides uniform precursors for subsequent reactions; thus avoiding crystal defects caused by excessive ion concentration gradients and ensuring that the formed precursor particles have uniform particle size and structure

[0063] After the dropwise addition is completed, stirring is continued for 30 to 60 minutes to make the reaction system fully uniform. Prolonging the stirring time can fully mix the Bi source and the Mo source, further stabilize the chemical environment of the reaction system, and avoid incomplete reaction caused by excessive or insufficient local ion concentration.

[0064] Please see attached Figure 1 In a preferred embodiment of the present invention, the step of adjusting the pH of the mixed solution comprises:

[0065] 1.5-4.0 mol / L NaOH solution is added dropwise to the mixed solution. The NaOH solution is used to adjust the acidity and alkalinity of the mixed solution. By adding dropwise, OH can be slowly released in the solution. - , and Bi in solution 3+ and Mo 6+ The ions react evenly to avoid local oversaturation caused by excessive alkalinity or too fast reaction;

[0066] Real-time monitoring of the pH value of the solution can timely adjust the addition rate to ensure that the solution is always in the best chemical environment, ensuring that the formed precursor structure is uniform and stable, and providing a suitable chemical environment for subsequent crystal growth;

[0067] After the adjustment is completed, stirring is continued for 30 minutes to stabilize the solution. Stirring for 30 minutes not only enhances the uniformity of the solution, but also further improves the chemical stability of the reaction system, reduces local concentration fluctuations during the precursor formation process, and lays the foundation for the selective growth of crystals.

[0068] Please see attached Figure 1 In a preferred embodiment of the present invention, the step of adding potassium ferrocyanide to the mixed solution comprises:

[0069] Add 0.01-0.1 mmol potassium ferrocyanide K3[Fe(CN)6], potassium ferrocyanide acts as a crystal surface regulator, and dissociates [Fe(CN)6] in the solution. 3- anions, which can be3+ and Mo 6+ The chemical environment around the ions regulates the preferential growth of specific crystal faces, thereby promoting the preferential growth of the 002 crystal face, forming a BMO catalyst with a two-dimensional nanosheet structure and improving its piezoelectric properties;

[0070] Stirring for 10 to 20 minutes ensures that potassium ferrocyanide is evenly distributed in the solution for regulating the growth of the crystal surface. Stirring makes potassium ferrocyanide evenly distributed, improves the consistency of crystal surface regulation, reduces crystal defects caused by local uneven concentration, and further optimizes the structure and performance of the catalyst.

[0071] Please see attached Figure 1 In a preferred embodiment of the present invention, the step of hydrothermal reaction comprises:

[0072] The treated mixed solution is transferred to a polytetrafluoroethylene-lined high-pressure reactor. The use of a polytetrafluoroethylene-lined reactor not only ensures the stability of the reaction environment, but also provides suitable pressure conditions for crystal growth, which helps to achieve uniform crystal surface growth;

[0073] The reaction is carried out at 180-200°C for 10-15 hours. The hydrothermal reaction promotes the growth and directional arrangement of crystals through the directional migration and crystallization process of ions in the solution under high temperature and high pressure conditions. This temperature can accelerate the diffusion of ions and the reaction rate. This time helps to further optimize the crystal surface structure, thereby improving the structural integrity and piezoelectric properties of the catalyst.

[0074] After the reaction is completed, the material is cooled to room temperature. The natural cooling process helps to avoid the internal stress damage of the crystal caused by rapid cooling. At the same time, slow cooling can further stabilize the crystal structure and improve the crystallinity and purity of the material.

[0075] Please see attached Figure 1 In a preferred embodiment of the present invention, the step of processing the product after cooling comprises:

[0076] Use anhydrous ethanol and deionized water for alternating washing, with each washing volume of 20-50 mL, for a total of three washes. Anhydrous ethanol can effectively remove organic residues in the product after the hydrothermal reaction and some by-products attached to the surface. At the same time, deionized water is used to further clean ionic impurities. By alternating washing, it is ensured that there are no residual impurities on the surface of the product, which improves the purity and quality of Bi2MoO6 crystals and lays the foundation for subsequent performance optimization.

[0077] The washed product is placed in an oven and dried at 60-80°C for 10-12 hours. Vacuum drying can reduce the boiling point of water and residual solvents, accelerate volatilization, and reduce the risk of high-temperature oxidation. Controlling the drying temperature between 60 and 80°C can not only effectively remove residual moisture, but also avoid changes in the morphology or crystal structure of the crystals due to excessively high temperatures.

[0078] Please see attached Figure 1 In a preferred embodiment of the present invention, the Bi2MoO6 catalyst with a specific crystal plane structure comprises:

[0079] When the crystal face is 002, the catalyst is in the form of a two-dimensional nanosheet with a band gap range of 2.1 to 2.5 eV. The preferential growth of the 002 crystal face is attributed to the regulation of potassium ferrocyanide, which promotes the stable growth of the 002 crystal face under high temperature and high pressure conditions by changing the surface energy and local charge distribution of the crystal surface. The two-dimensional nanosheet structure provides a larger specific surface area and a more efficient electron transfer path;

[0080] When the crystal face is 131, the catalyst is blocky and its band gap ranges from 2.7 to 3.1 eV. The formation of the 131 crystal face is not affected by the crystal face regulator and grows into a block structure under natural conditions. Its higher band gap reflects the lower electron transition efficiency and mechanical strength. By regulating the growth of different crystal faces, the crystal face structure and morphology of the catalyst can be customized according to actual application requirements, providing a variety of options for optimizing the piezoelectric properties, catalytic efficiency and durability of Bi2MoO6.

[0081] Please see attached Figure 1 In a preferred embodiment of the present invention, the mixed solution pretreatment step comprises:

[0082] The mixed solution is placed under ultrasonic conditions for 10 minutes and then stirred for 10-20 minutes to promote the full dissolution and dispersion of the substances in the precursor, to promote the full mixing and uniform dispersion of the precursor. Ultrasound can accelerate the diffusion of ions in the solution, improve the activity of the reactants, and promote the initial formation of precursor particles. At the same time, constant temperature maintenance and stirring can prevent local excessive temperature or ion enrichment, thereby ensuring the uniformity of the system and reducing crystal defects caused by uneven initial reaction conditions;

[0083] During ultrasonic stirring, the pH value of the mixed solution is maintained stable at 5-7 to ensure the chemical stability of each component in the solution. By changing to controlling the pH value of the solution during ultrasonication, abnormal ion reactions caused by an unstable chemical environment are avoided, the structural uniformity and chemical stability of the precursor are improved, and the initial growth conditions of the crystal are optimized.

[0084] The present invention also includes an application method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes. The BMO piezoelectric catalyst includes but is not limited to application in the degradation of 2,4-dichlorophenol (2,4-DCP):

[0085] The initial concentration of the target pollutant was 10 mg / L, and the catalyst dosage was 100 mg;

[0086] An ultrasonic generator was used to provide external stress, with an ultrasonic frequency of 40kHz and a power of 100W;

[0087] Under the above conditions, the degradation efficiency exceeded 96%.

[0088] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.

[0089] Example 1: Preparation method for regulating crystal surface growth by adding potassium ferrocyanide

[0090] Implementation steps:

[0091] Prepare Bi suspension and Mo source solution:

[0092] Weigh 2 mmol of Bi(NO3)3·5H2O and 1 mmol of Na2MoO6·2H2O, mix gradually and adjust the pH to 6.

[0093] Adding crystal surface modifier:

[0094] Add 0.05 mmol potassium ferrocyanide K3[Fe(CN)6] to the mixed solution and stir for 20 minutes.

[0095] Hydrothermal reaction:

[0096] The reaction was carried out at 180 °C for 12 h.

[0097] Washing and drying:

[0098] The product was washed alternately with anhydrous ethanol and deionized water three times and dried in an oven at 60°C for 12 h.

[0099] result:

[0100] Crystal structure: XRD analysis showed that the strength of the 002 crystal plane was significantly enhanced, and SEM showed that the product was a two-dimensional nanosheet structure.

[0101] Performance: The band gap is 2.3eV, and the piezoelectric catalytic performance shows a degradation efficiency of more than 96% in the 2,4-DCP degradation experiment.

[0102] Example 2: Preparation method without adding potassium ferrocyanide

[0103] Operation process

[0104] Solution preparation:

[0105] The same Bi source and Mo source solutions as in Example 1 were prepared, mixed and the pH was adjusted to 6.

[0106] No crystal surface modifier:

[0107] Skip the potassium ferrocyanide addition step and stir only for 20 minutes.

[0108] Hydrothermal reaction:

[0109] The reaction was carried out at 180 °C for 12 h.

[0110] Washing and drying:

[0111] Wash and dry according to the method of Example 1.

[0112] result:

[0113] Crystal structure: XRD showed that the 131 crystal plane was dominant, and SEM showed that the product had a block structure.

[0114] Performance: The band gap is 2.9 eV and the efficiency of piezoelectric catalytic performance for 2,4-DCP degradation is less than 80%.

[0115] Example 3: Preparation method by adding potassium ferrocyanide and optimizing hydrothermal conditions

[0116] Operation process

[0117] Solution preparation:

[0118] The same Bi source and Mo source solutions as in Example 1 were prepared, mixed and the pH was adjusted to 6.

[0119] Adding crystal surface modifier:

[0120] Add 0.05 mmol potassium ferrocyanide to the solution and stir for 20 minutes.

[0121] Optimize hydrothermal conditions:

[0122] The reaction temperature was increased to 200°C and the time was extended to 15 hours.

[0123] Washing and drying:

[0124] Wash and dry according to the method of Example 1.

[0125] result:

[0126] Crystal structure: XRD shows that the advantage of 002 crystal plane is further improved, and SEM shows that the thickness of the nanosheet is thinner and the specific surface area is increased.

[0127] Performance: The band gap is 2.1eV, the piezoelectric catalytic performance is improved, and the degradation efficiency of 2,4-DCP is as high as 98%.

[0128] Comparative experiment 1: Crystal growth control experimental test

[0129] Experimental purpose: To verify the role of potassium ferrocyanide in regulating the growth direction and morphology of Bi2MoO6 crystals.

[0130] Experimental setup

[0131] Experimental Group:

[0132] 0.05 mmol potassium ferrocyanide was added, the pH was adjusted to 6, and the reaction was carried out hydrothermally at 180°C for 12 hours.

[0133] Control group 1:

[0134] No potassium ferrocyanide was added, and other conditions were the same.

[0135] Control group 2:

[0136] Add 0.01 mmol potassium ferrocyanide, and other conditions remain the same.

[0137] Experimental procedures

[0138] Solution preparation:

[0139] Prepare 2 mmol Bi(NO3)3·5H2O solution and 1 mmol Na2MoO6·2H2O solution respectively, add the Mo source solution dropwise into the Bi suspension and mix well.

[0140] pH adjustment:

[0141] The pH of the mixed solution was adjusted to 6 with 3 mol / L NaOH.

[0142] Crystal surface modifier addition:

[0143] According to the group settings, different concentrations of potassium ferrocyanide were added and stirred for 20 minutes.

[0144] Hydrothermal reaction:

[0145] The mixed solution was transferred into a 100 mL polytetrafluoroethylene-lined autoclave and reacted at 180° C. for 12 hours.

[0146] Washing and drying:

[0147] After the reaction was completed, the mixture was cooled to room temperature, washed alternately with anhydrous ethanol and deionized water three times, and dried in vacuum for 12 hours.

[0148] Test analysis:

[0149] XRD was used to characterize the crystal growth direction, and SEM was used to observe the crystal morphology.

[0150] The comparative experimental data are shown in Table 1:

[0151] Table 1 XRD crystal plane intensity and SEM morphology analysis results

[0152]

[0153]

[0154] From the data in Table 1, we can get:

[0155] Experimental Group:

[0156] After adding potassium ferrocyanide, the strength of the 002 crystal plane is significantly higher than that of the 131 crystal plane. SEM shows that the product is a two-dimensional nanosheet with uniform crystal morphology and large specific surface area, which provides a better structural basis for piezoelectric catalytic performance.

[0157] Control group 1:

[0158] When potassium ferrocyanide was not added, the 131 crystal plane became dominant, with an intensity about twice that of the 002 crystal plane. SEM showed that the product was blocky and irregular in morphology, and the crystal growth lacked directionality.

[0159] Control group 2:

[0160] When a lower concentration of potassium ferrocyanide is added, the intensity of the 002 and 131 crystal planes is similar, and SEM shows a mixed morphology, and the regulation effect is limited.

[0161] Comparative experiment 2: Catalytic performance test experiment

[0162] Experimental purpose: To verify the effect of potassium ferrocyanide on regulating crystal surface growth and improving the piezoelectric catalytic performance of the catalyst.

[0163] Experimental setup

[0164] Experimental group (the present invention):

[0165] Add 0.05 mmol potassium ferrocyanide to prepare a two-dimensional nanosheet 002 crystal surface catalyst.

[0166] Control group 1:

[0167] The block 131 crystal surface catalyst was prepared without adding potassium ferrocyanide.

[0168] Control group 2:

[0169] Add 0.01 mmol potassium ferrocyanide to regulate the mixed crystal surface catalyst with insufficient effect.

[0170] Experimental procedures

[0171] Catalyst preparation:

[0172] Bi2MoO6 catalyst was prepared according to different group settings (for specific preparation methods, please refer to the crystal surface regulation experiment settings).

[0173] Degradation target pollutants:

[0174] Prepare a 10 mg / L 2,4-dichlorophenol (2,4-DCP) solution and place 100 mL in a reaction container.

[0175] Catalytic reaction conditions:

[0176] 100 mg of catalyst was added, and an ultrasonic generator was used to provide external stress to ensure that there was no light throughout the process.

[0177] Degradation performance determination:

[0178] Samples were taken every 10 minutes, and the residual concentration of 2,4-DCP was determined by high performance liquid chromatography (HPLC), and the degradation rate and degradation rate constant k were calculated.

[0179] The comparative experimental data are shown in Table 2:

[0180] Table 2 Catalyst degradation performance data for 2,4-DCP

[0181]

[0182] From the data in Table 2, we can get:

[0183] Experimental group (the present invention):

[0184] The catalyst with 0.05 mmol potassium ferrocyanide added showed the highest degradation efficiency (96.2%) and the fastest degradation rate constant (k = 0.060 min -1 ), indicating that the two-dimensional nanosheet 002 crystal facet significantly improves the number of active sites and piezoelectric catalytic performance.

[0185] Control group 1:

[0186] The degradation efficiency of the catalyst without potassium ferrocyanide was only 74.5%, and the degradation rate was slow (k = 0.035min -1 ), showing low activity of the typical bulk 131 crystal plane structure.

[0187] Control group 2:

[0188] The catalyst degradation efficiency of adding 0.01 mmol potassium ferrocyanide was 85.3%, and the rate constant was 0.045 min -1 ,Although the performance has been improved, it still has not reached the level of the experimental group, indicating that the concentration of potassium ferrocyanide is not enough to fully regulate the crystal surface growth.

[0189] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes, characterized in that: The following steps are involved: Prepare Bi suspension and Mo source solution; The Mo source solution is slowly added to the Bi suspension under stirring conditions to form a uniform mixed solution; Adjust the pH of the mixed solution to 5-7 with sodium hydroxide solution; adding potassium ferrocyanide as a crystal surface regulating agent to the mixed solution; Mixed solution pretreatment; placing the treated mixed solution in a high pressure reactor for hydrothermal reaction; After cooling to room temperature, the reaction product was collected, washed with anhydrous ethanol and deionized water in sequence, and dried to obtain a Bi2MoO6 catalyst with a specific crystal face structure.

2. The method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes according to claim 1, characterized in that: The preparation of Bi suspension and Mo source solution includes: 1.25-1.75 mmol of (Bi(NO3)3·5H2O) was dissolved in 30 mL of deionized water, and Bi particles were uniformly dispersed using ultrasound to obtain a Bi suspension; Dissolve 0.25-0.75 mmol of sodium molybdate (Na2MoO6·2H2O) in 100 mL of deionized water and stir for 5-10 minutes until it is completely dissolved to obtain a Mo source solution.

3. The method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes according to claim 1, characterized in that: The steps of mixing the solution include: Under magnetic stirring, slowly add the Mo source solution at a rate of 5-10 mL / min; After the dropwise addition is completed, stirring is continued for 30 to 60 minutes to make the reaction system fully uniform.

4. The method for preparing a BMO piezoelectric catalyst rapidly grown on different crystal planes according to claim 1, characterized in that: The steps of adjusting the pH of the mixed solution include: Use 1.5-4.0 mol / L NaOH solution to add dropwise into the mixed solution; Real-time monitoring of the pH value of the solution; After the conditioning was completed, stirring was continued for 30 minutes to stabilize the solution.

5. The method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes according to claim 1, characterized in that: The steps of adding potassium ferrocyanide to the mixed solution include: Add 0.01-0.1 mmol potassium ferrocyanide [K3Fe(CN6)]; Stir for 10 to 20 minutes to ensure that potassium ferrocyanide is evenly distributed in the solution to regulate the growth of the crystal surface.

6. The method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes according to claim 1, characterized in that: The steps of the hydrothermal reaction include: The treated mixed solution is transferred to a polytetrafluoroethylene-lined autoclave; The reaction is carried out at 180 to 200° C. for 10 to 15 hours; After the reaction was completed, it was cooled to room temperature.

7. The method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes according to claim 1, characterized in that: The steps of processing the cooled product include: Wash alternately with anhydrous ethanol and deionized water, with each wash volume of 20-50 mL, for a total of three washes; The washed product is placed in an oven and dried at 60-80°C for 10-12 hours.

8. The method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes according to claim 1, characterized in that: Bi2MoO6 catalysts with specific crystal plane structures include: When the crystal plane is 002, the catalyst appears as a two-dimensional nanosheet with a band gap ranging from 2.1 to 2.5 eV; When the crystal plane is 131, the catalyst is in block form and its band gap ranges from 2.7 to 3.1 eV.

9. The method for rapidly preparing a BMO piezoelectric catalyst grown on different crystal planes according to claim 1, characterized in that: The mixed solution pretreatment steps include: The mixed solution is subjected to ultrasonication for 10 minutes and then stirred for 10 to 20 minutes to promote the full dissolution and dispersion of the substances in the precursor to promote the full mixing and uniform dispersion of the precursor; During the ultrasonic stirring process, the pH value of the mixed solution is maintained stable at 5 to 7 to ensure the chemical stability of each component in the solution.

10. An application method for rapidly preparing BMO piezoelectric catalysts grown on different crystal planes, characterized in that: The method for preparing a BMO piezoelectric catalyst with different crystal plane growth quickly according to any one of claims 1 to 9, wherein the BMO piezoelectric catalyst includes but is not limited to the application in the degradation of 2,4-dichlorophenol (2,4-DCP): The initial concentration of the target pollutant was 10 mg / L, and the catalyst dosage was 100 mg; An ultrasonic generator was used to provide external stress, with an ultrasonic frequency of 40kHz and a power of 100W; Under the above conditions, the degradation efficiency exceeded 96%.